Nickel-Catalyzed Hydrogenolysis and Conjugate Addition of 2-Hydroxymethylpyridines via Organozinc Intermediates - Hanna, Luke E. (Org Lett, 2017)
2-Hydroxymethylpyridines undergo nickel-catalyzed hydrogenolysis upon activation with a chlorophosphate. Reactions employ diethylzinc and are proposed to proceed through secondary benzylzinc reagents. Quenching with deuteromethanol provides straightforward incorporation of a deuterium label in the benzylic position. Intramolecular conjugate additions with α,β-unsaturated esters are also demonstrated and support the intermediacy of a benzylzinc complex.